МАМЛАКАТИМИЗДА ИҚТИСОДИЁТ СОҲАСИНИ РИВОЖЛАНТИРИШДА ИЖТИМОИЙ ТАРМОҚЛАР (ТИББИЁТ, ФАН, ТАЪЛИМ)НИНГ ЎРНИ - kariyeva, Halima (FILOLOGIYA UFQLARI JURNALI, 2021)
In this article the development of the economy and social networks in the field of economics are given on the example of medical, service, educftional institutions.